Teachers' Readiness for English Language Teaching in the Post-Print Culture - Fathia, Rahma; Suparman, Asep; Hamzah, Amir (Lembaga Riset dan Inovasi Almatani, 2026)
The rapid shift in English Language Teaching (ELT) from traditional print-based materials to digital and AI-based environments requires a comprehensive evaluation of teacher readiness. This study investigates ELT teachers' readiness for post-print pedagogy in four constructs: knowledge and skills, affective/beliefs, context, and behavior, and explores the influence of demographic variables. Using a quantitative, descriptive, and comparative design, 228 active English teachers in Indonesia participated via an online questionnaire. The findings reveal a